If Q is the Mean Proportional Between P and R, Show That: Pqr (P + Q + R)3 = (Pq + Qr + Rp)3 - Mathematics
If q is the mean proportional between p and r, show that: pqr (p + q + r)3 = (pq + qr + rp)3
Given, q is the mean proportional between p and r.
⇒ q2 = pr
L.HS = `pqr(p + q + r)^3`
`= qq^2 (p + q + r)^3` [∵ q^2 = pr]
`= [q(p + q + r)]^3`
`= (pq + q^2 + qr)^3`
`= (pq + pr + qr)^3` ` [∵ q^2 = pr]`
Is there an error in this question or solution?
why create a profile on Shaalaa.com?
1. Inform you about time table of exam.
2. Inform you about new question papers.
3. New video tutorials information.